IMPROVING EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL CULTURE, LEADERSHIP, AND WORK MOTIVATION: SURVEY ON BANKING ORGANIZATIONS IN SOUTHEAST SULAWESI - Wa Ode Zusnita Muizu; Diana Sari (Jurnal Bisnis Manajemen, 2019)
This research aims to identify the effect of organization culture, leadership, and work motivation on employee performance of banking organizations in Southeast Sulawesi. The methods used in this research are a descriptive survey and explanatory survey. Hypotheses testing was conducted using the Structural Equation Model (SEM). Meanwhile, data processing was done using Lisrel 8.72 program. The first hypotheses test result showed that organizational culture has a significant and positive effect on leadership. The second hypotheses test result showed that organizational culture has a significant and positive effect on employee work motivation. The third hypotheses test result showed that organizational culture and leadership have significant effects, both partially and simultaneously, on work motivation. The fourth hypotheses test result showed that organizational culture, leadership, and work motivation have a significant effect, both partially and simultaneously, on employee performance.